Development of big book media on songket weaving activities in Riau for elementary school - Ayu Nur Umiroh; Laili Rahmi (Himpunan Pengembang Kurikulum Indonesia, 2025)
The lack of engaging learning media is one of the challenges in the teaching and learning process. This study aims to describe the development process and produce a Big Book themed on weaving songket fabric from Riau, integrated into the lesson on muscle force and friction for fourth-grade elementary students. This research uses the 4D development model (Define, Design, Develop, and Disseminate). The subjects involved six validators: two material experts, two language experts, and two design experts. Data collection was conducted through validation sheets for each expert field. The data were analyzed using qualitative and quantitative methods. The results showed that the developed Big Book media is highly valid and suitable for use in IPAS learning. Material experts confirmed that the content is appropriate and relevant to the curriculum, language experts stated that the language is clear and easy for students to understand, and design experts noted that the visuals are attractive and support the learning objectives. Overall, the Big Book was assessed as interesting, communicative, and easy to follow. Additionally, it effectively connects the science concepts of muscle and friction forces with local cultural wisdom through the traditional activity of songket weaving, making learning more contextual and meaningful for students. Abstrak Kurangnya media pembelajaran yang menarik menjadi salah satu kendala dalam proses belajar mengajar. Penelitian ini bertujuan untuk mendeskripsikan proses dan menghasilkan media Big Book bertema kegiatan menenun kain songket Riau pada materi gaya otot dan gaya gesek untuk peserta didik kelas IV Sekolah Dasar. Penelitian ini merupakan jenis penelitian pengembangan dengan model 4D (Define, Design, Develop, dan Disseminate). Subjek penelitian meliputi enam validator, yaitu dua ahli materi, dua ahli bahasa, dan dua ahli desain. Teknik dan instrumen pengumpulan data dalam penelitian ini berupa lembar validasi ahli materi, lembar validasi ahli bahasa dan lembar validasi ahli desain. Teknik analisis data yang digunakan dalam penelitian ini adalah analisis data kualitatif dan analisis data kuantitatif. Berdasarkan hasil penelitian dapat disimpulkan bahwa media big book dinyatakan sangat valid dan layak digunakan dalam proses pembelajaran IPAS. Hasil validasi menunjukkan bahwa media dinilai sangat valid oleh para ahli. Ahli materi menilai isi sudah sesuai dan layak, ahli bahasa menyatakan bahasanya mudah dipahami peserta didik, dan ahli desain menilai tampilannya menarik serta mendukung pembelajaran. Media big book ini dinilai menarik, komunikatif, mudah dipahami, dan mampu mengaitkan materi pembelajaran gaya gesek dan gaya otot dengan kearifan lokal melalui kegiatan menenun kain songket Riau. Kata Kunci: gaya gesek; gaya otot; media big book; menenun kain songket